PRODUKTIVITAS LISTRIK MICROBIAL FUEL CELL PADA SUBSTRAT LIMBAH AIR REBUSAN MIE INSTAN - Zulfikar, Erwin Satria (JTAM ROTARY, 2021)
In this modern age the need for energy is increasing. This will trigger energy activists to continue to innovate in developing appropriate and efficient alternative energy. One of technology that has the potential to be developed is a Microbial Fuel Cell (MFC) that utilizes microorganisms as catalysts to degrade organic compounds to produce electricity. This experiment focuses on the influence of the incubation time of the waste substrate of instant noodle stew water and the addition of an aerator as an addition to the oxygen compound in the cathode section. The incubation variations carried out in this study were 1 day, 3 days and 7 days. The optimal electricity production results were obtained from a variation of 7 days incubation with currents and voltages of 528 mA and 627 mV, while the incubation of 1 day electric current and maximum voltage obtained were 274 mA and 540 mV. At 3 days incubation of electric current and the maximum voltage is 390 mA and 588 mV. 3. The addition of aerators to the system greatly affects the system, which has an impact on increasing the current and voltage in the Microbial Fuel Cell. Keywords:Electricity, Microorganism, Incubation, Current, Voltage